Туала сяртчы: школа театръеслы юрттэт: сценарийёс, сценкаос,пьеса / У. Ш. Бадретдинов - Бадретдинов Ульфат Шайхутдинович (Удмуртия, 2023)
Экземпляры: мл. аб. (2024) / Инвентарный номер: 59921 / Цена: / Сис.шифр: К84(2Рос=Удм)-6 / Авт.знак: Б 15 / ББК: 84(2Рос=Удм)-6